Bladder Urothelial Carcinoma in a Child: Case Report and Review of Literature - Oda, Marian Hanae; dos Santos, Danilo Vicente; Farias, Adria Karina; de Oliveira, Leilane; Falcão, Bruno Pinheiro; Ahn, Nicholas J.; Amarante, Antônio Carlos; Losso, Graziele Moraes; Dias, Andre Ivan Bradley dos Santos; Agulham, Miguel Angelo; Fachin, Camila Girardi (Frontiers in Pediatrics, 2019)
Bladder urothelial carcinoma (UC) it is the fifth most prevalent carcinoma in humans, nevertheless in children and young adults it's very rare. It usually occurs in older adults. Literature on UC in pediatric population is limited and important information (risk factors, follow-up protocols, etc.) are poorly defined. We present an 11-year-old boy with a painful macroscopic hematuria. Ultrasound revealed a heterogeneous intravesical mass without extravesical extension, which was confirmed by computed tomography (CT) and magnetic resonance imaging (MRI). The first biopsy was compatible with urothelial papilloma. After 1 year, he returned with a bigger mass. Transurethral resection of the bladder (TURB) was performed and immunohistochemistry showed low-grade papillary UC with a high-grade component, with tumor free margin. Tumor had mutations in the BRAF and KRAS genes. Two and a half years after the resection the patient has no recurrence. Less than 1% of bladder UC occur in the first two decades of life. Gross hematuria is a common symptom. Ultrasound is generally the first diagnostic tool. MRI is also helpful, but cystoscopy allows definitive diagnosis. Transurethral resection of the bladder (TURB) is the standard treatment, with good results and low recurrence rate, and it was the treatment of choice for our patient, that remains free of disease. The BRAF and KRAS gene mutations were never described before in pediatric UC. There are only few cases in literature of pediatric UC that present a tumor genetic profile; therefore, our case report adds more information to this very rare disease in children.